2015
DOI: 10.1007/s40299-015-0265-y
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Decision-Making About Postgraduate Education at G University in China: The Main Factors and the Role of Family and of Teachers

Abstract: The paper draws on findings from a case study which explored factors influencing students' decisionmaking of postgraduate (PG) education at G University in China. Both questionnaires and follow-up interviews were used for data collection. This paper reports the main reasons for students' choices of subject and institution for PG education, and the influences of families and teachers, and of guanxi in their decision-making. The findings show that both families and teachers play important roles in shaping studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 31 publications
6
21
0
5
Order By: Relevance
“…This section will further discuss the findings in association with the socioeconomic, cultural, and political issues of Vietnam and relevant literature in the field of education. All 12 motivational factors identified in this study are consistent with the existing literature (e.g., English et al, 2016;Liu & Morgan, 2016;Nguyen, 2013). Pull factors appeared to influence Vietnamese students' decision to study abroad more strongly than push factors did.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This section will further discuss the findings in association with the socioeconomic, cultural, and political issues of Vietnam and relevant literature in the field of education. All 12 motivational factors identified in this study are consistent with the existing literature (e.g., English et al, 2016;Liu & Morgan, 2016;Nguyen, 2013). Pull factors appeared to influence Vietnamese students' decision to study abroad more strongly than push factors did.…”
Section: Discussionsupporting
confidence: 88%
“…Pull factors consist of factors in the host country or institution that attract international students (Mazzarol & Soutar, 2002), such as culture, living standards, socioeconomic status of the host country, improved career prospects, and immigration opportunities. Other studies that do not use the push-pull model have reached similar conclusions and further revealed that international students' decisions to study abroad can be influenced by their family, teachers, and other socioeconomic, political, and cultural issues in both the home and host countries (e.g., English, Allison, & Ma, 2016;Liu & Morgan, 2016;Nguyen, 2013;Spinks, 2016).…”
Section: Students' Motivation For International Education and Migrationmentioning
confidence: 68%
See 1 more Smart Citation
“…In China, potential postgraduate students considered personal interest, employability, good income prospects, entry requirements, reputation, location, teaching quality and facilities as factors that underpinned their choice of a Chinese University (Liu & Morgan, 2015). In the UK the following choice criteria for potential postgraduate students (in order of importance) were unveiled (Soilemetzidis, Bennett, & Leman, 2014): HEI location, HEI reputation, course content and reputation of the subject area/department.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bu çalışma ayrıca Bourdieu'nun diğer bir anahtar kavramı olan toplumsal sermaye kavramına yer vermektedir. Çin bağlamında öğrencilerin yükseköğrenim tercihlerine etki eden ana sebepler olarak bu üç etkinin bir arada araştırıldığı sadece bir çalışma (Liu ve Morgan, 2016) bulunmaktadır. Lise düzeyinde ise öğrencilerin sanat eğitimi tercihleri üzerine yapılmış ve bu üç etkinin bir arada yer aldığı bir çalışma bulunmamaktadır.…”
Section: Introductionunclassified